The development and initial psychometric evaluation of a measure assessing adherence to prescribed exercise: the Exercise Adherence Rating Scale (EARS). Issue 2 (June 2017) - Newman-Beinart, Naomi A.; Norton, Sam; Dowling, Dominic; Gavriloff, Dimitri; Vari, Chiara; Weinman, John A.; Godfrey, Emma L.
Abstract: Objectives: There is no gold standard for measuring adherence to prescribed home exercise. Self-report diaries are commonly used however lack of standardisation, inaccurate recall and self-presentation bias limit their validity. A valid and reliable tool to assess exercise adherence behaviour is required. Consequently, this article reports the development and psychometric evaluation of the Exercise Adherence Rating Scale (EARS). Design: Development of a questionnaire. Setting: Secondary care in physiotherapy departments of three hospitals. Participants: A focus group consisting of 8 patients with chronic low back pain (CLBP) and 2 physiotherapists was conducted to generate qualitative data. Following on from this, a convenience sample of 224 people with CLBP completed the initial 16-item EARS for purposes of subsequent validity and reliability analyses. Methods: Construct validity was explored using exploratory factor analysis and item response theory. Test-retest reliability was assessed 3 weeks later in a sub-sample of patients. Results: An item pool consisting of 6 items was found suitable for factor analysis. Examination of the scale structure of these 6 items revealed a one factor solution explaining a total of 71% of the variance in adherence to exercise. The six items formed a unidimensional scale that showed good measurement properties, including acceptable internal consistency and high test-retest reliability. Conclusions: The EARS enables the measurement of adherence to prescribed home exercise. This may facilitate the evaluation of interventions promoting self-management for both the prevention and treatment of chronic conditions.